2014
DOI: 10.1007/s11906-013-0414-8
|View full text |Cite
|
Sign up to set email alerts
|

Converging Indications of Aldosterone Antagonists (Spironolactone and Eplerenone): A Narrative Review of Safety Profiles

Abstract: The converging clinical effectiveness of mineralocorticoid receptor antagonists (MRAs) Spironolactone and Eplerenone has made their safety profiles/cost-effectiveness key determinants of "agents of choice" across a broad range of clinical indications. The clinical biology of the aldosterone molecule and its range of effects in varied organ systems have been well elucidated from recent mechanistic and systematic studies. Clinical experience with Spironolactone is well established, as is its adverse effects prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 52 publications
2
22
0
4
Order By: Relevance
“…These findings corroborate previous clinical data of MR antagonists in other medical conditions, particularly systemic hypertension and heart failure [8,9,10,11]. Eplerenone has been associated with fewer side effects than spironolactone in multiple reports evaluating its use, and this has been attributed to its higher selectivity for the aldosterone receptor [7].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These findings corroborate previous clinical data of MR antagonists in other medical conditions, particularly systemic hypertension and heart failure [8,9,10,11]. Eplerenone has been associated with fewer side effects than spironolactone in multiple reports evaluating its use, and this has been attributed to its higher selectivity for the aldosterone receptor [7].…”
Section: Discussionsupporting
confidence: 88%
“…Studies have suggested a significant increase in side effects with chronic MR antagonist exposure, even with eplerenone (up to 47% in one study), emphasizing its judicious use and need for tapering upon clinical stability [8,9,10,11]…”
Section: Discussionmentioning
confidence: 99%
“…Thus, as shown in Scheme 14, performing the reaction in a refluxing ethanol/water (1:1 v/v) mixture, and using a very low catalyst loading of 0.0001 mol%, atenolol could be selectively obtained in 93% yield [64]. The steroidal compound eplerenone (60) is an orally-active aldosterone antagonist featuring a canrenone-type structure that is also used for the treatment of hypertension and heart failure [65,66]. The synthesis of 60 has been the subject of several patents.…”
Section: Application Of Complex [Pth{(pme 2 O) 2 H}(pme 2 Oh)] In Thementioning
confidence: 99%
“…Eplerenone is the first of a new class of drugs known as selective aldosterone receptor antagonists in minimal manner blocked steroid receptors, and thereby minimizing many of the hormonal side effects seen with spironolactone [27]. Overall eplerenone has been demonstrated better profile of safety and tolerability than spironolactone [28]. The antihypertensive efficacy of both drugs are probably similar, but eplerenone shown a significant renoprotective effect in diabetic patients with hypertension [29].…”
Section: Non Selective Versus Selective Mineralocorticoid Receptor Anmentioning
confidence: 99%